IMPLEMENTASI METODE TALAQQI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ALQURAN PESERTA DIDIK MTS DI BEKASI - Azzahro, Athiyah; Sumirah, Ade; Dhinda Annisa Sholehah, Marwah (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This study aims to examine the effectiveness of the talaqqi method in improving the Qur’an reading ability of junior high school students in Bekasi. The research background is the low ability of students to read the Qur’an correctly, particularly regarding proper pronunciation (makhraj), application of tajwid rules, and fluency, requiring a systematic and interactive learning method. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. The research subjects were junior high school students participating in Qur’an reading classes. Data were collected through observation, reading tests, and documentation and analyzed using descriptive qualitative and simple quantitative methods. The results show that in the pre-cycle, students’ Qur’an reading ability was low, with many errors in pronunciation and tajwid. After implementing the talaqqi method in Cycle I, there was an improvement, but mastery was not fully achieved. In Cycle II, with more structured implementation and reinforced corrections, students showed significant improvement; the average reading score reached the good category with 85% completeness. This study demonstrates that the talaqqi method effectively improves Qur’an reading ability, as well as student engagement and self-confidence. It is recommended for teachers to routinely apply the talaqqi method in Qur’an learning, and future research may evaluate the long-term impact on Qur’an memorization and religious character development.